Adolescent Major Depressive Disorder: Neuroimaging Evidence of Sex Difference during an Affective Go/No-Go Task - Chuang, Jie-Yu; Hagan, Cindy C.; Murray, Graham K.; Graham, Julia M. E.; Ooi, Cinly; Tait, Roger; Holt, Rosemary J.; Elliott, Rebecca; van Nieuwenhuizen, Adrienne O.; Bullmore, Edward T.; Lennox, Belinda R.; Sahakian, Barbara J.; et al. (Frontiers in Psychiatry, 2017)
Compared to female major depressive disorder, male major depressive disorder often receives less attention. However, research is warranted since there are significant sex differences in the clinical presentation of major depressive disorder and a higher rate of suicide in depressed men. To our knowledge, this is the first functional magnetic resonance imaging (fMRI) study with a large sample addressing putative sex differences in major depressive disorder during adolescence, a period when one of the most robust findings in psychiatric epidemiology emerges; that females are twice as likely to suffer from major depressive disorder than males. Twenty-four depressed and 10 healthy male adolescents, together with 82 depressed and 24 healthy female adolescents, aged 11 to 18 years, undertook an affective go/no-go task during fMRI acquisition. In response to sad relative to neutral distractors, significant sex differences (in the supramarginal gyrus) and group-by-sex interactions (in the supramarginal gyrus and the posterior cingulate cortex) were found. Furthermore, in contrast to the healthy male adolescents, depressed male adolescents showed decreased activation in the cerebellum with a significant group-by-age interaction in connectivity. Future research may consider altered developmental trajectories and the possible implications of sex-specific treatment and prevention strategies for major depressive disorder.